Search for exclusive Z-boson production and observation of high-mass pp̄→pγγp̄→pl+l-p̄ events in pp̄ collisions at s=1.96TeV - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2009)
This Letter presents a search for exclusive Z boson production in proton-antiproton collisions at s=1.96TeV, using the CDFII detector. No exclusive Z→l+l- candidates are observed and the first upper limit on the exclusive Z cross section in hadron collisions is found to be σexcl(Z)<0.96pb at 95% confidence level. In addition, eight candidate exclusive dilepton events from the process pp̄→pγγp̄ →pl+l-p̄ are observed, and a measurement of the cross section for Mll>40GeV/c2 and |ηl|<4 is found to be σ=0.24-0.10+0.13pb, which is consistent with the standard model prediction. © 2009 The American Physical Society.